Metal cooking utensil and preparation method thereof

By designing a bionic leaf vein-like concave-convex texture structure and a nanoparticle layer on metal cooking utensils, the problems of insufficient hydrophobicity and easy wear of the texture of metal cooking utensils are solved, achieving a more lasting anti-stick effect and more efficient moisture management.

CN120616295AActive Publication Date: 2025-09-12FOSHAN SHUNDE MIDEA ELECTRICAL HEATING APPLIANCES MFG CO LTD +1

Patent Information

Application Number
CN202511093977.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-06
Publication Date
2025-09-12
Estimated Expiration
2045-08-06

AI Technical Summary

Technical Problem

Existing metal cooking utensils are not hydrophobic enough, which causes food to stick easily and the texture structure to wear easily. They have unsatisfactory anti-stick performance and a short service life.

Method used

A concave-convex texture structure with a bionic leaf vein shape is combined with a nanoparticle layer and a hydrophobic material layer to form irregularly distributed convex rib units and concave units, establishing multi-directional water vapor channels and liquid storage spaces. The nanoparticle layer enhances hydrophobicity, and the hydrophobic material layer reduces surface energy.

Benefits of technology

Improves the anti-stick performance of metal cooking utensils and the wear resistance of the texture structure, extends the service life, and achieves more efficient dynamic moisture balance and surface hydrophobicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120616295A_ABST
    Figure CN120616295A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of kitchen utensils, in particular to a metal cooking utensil and a preparation method thereof. The invention provides a metal cooking utensil. The metal cooking utensil comprises a metal matrix layer, a nano-particle layer and a hydrophobic material layer. The metal matrix layer is provided with a concave-convex texture structure in a bionic vein form, the concave-convex texture structure comprises a plurality of convex rib units and concave units formed among the convex rib units, and the vertical projection shapes of any two adjacent convex rib units on the surface of the metal matrix layer are different from each other; the nano-particle layer covers the surface of the concave-convex texture in a shape-following manner; and the hydrophobic material layer covers the surface of the nanoparticle layer. According to the metal cooking utensil, the metal base body layer is provided with the concave-convex texture structure in the bionic vein form, the synergistic effect of the nano-particle layer and the hydrophobic material layer is combined, linear abrasion is reduced through the convex rib units distributed irregularly, meanwhile, the hydrophobicity is enhanced through the nano-structure, and therefore the metal cooking utensil is more environmentally friendly. The method has the advantages that the surface hydrophobicity is improved, the anti-sticking performance is enhanced, and the service life of the texture structure is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of kitchen utensils, and in particular to a metal cooking utensil and a preparation method thereof. Background Art

[0002] In existing technology, metal cooking utensils lack hydrophobicity due to their high surface energy. This can easily cause food to stick during cooking (such as rice sticking to the pan, food burning in the frying pan), as well as discoloration due to high temperatures. Existing solutions prevent sticking by creating a matrix of concave and convex dots or textures on the metal surface.

[0003] However, the concave-convex structures produced by existing technical solutions are limited to the micron level due to process limitations, resulting in limited improvement in surface hydrophobicity, resulting in unsatisfactory non-stick performance. Furthermore, this matrix-distributed concave-convex structure typically exhibits a distinct directional arrangement. In actual use, this textured structure is relatively weak, and is particularly susceptible to linear scratches from repeated friction with utensils such as spatulas. With increased use, the textured structure gradually degrades, resulting in a significant short-term decrease in anti-stick performance, making it difficult to meet the requirements of non-stick cookware. Summary of the Invention

[0004] The main purpose of the present invention is to provide a metal cooking utensil and a preparation method thereof, aiming to improve the problem of insufficient anti-stick durability of the concave-convex texture structure of existing cookware.

[0005] To achieve the above-mentioned objectives, an embodiment of the present invention provides a metal cooking utensil, comprising: a metal base layer having a concave-convex texture structure in the form of bionic leaf veins, the concave-convex texture structure comprising a plurality of rib units and concave units formed between the rib units, wherein the planar projection shapes of any two adjacent rib units in a direction perpendicular to the surface of the metal base layer are different from each other; A nanoparticle layer conformally covers the surface of the concave-convex texture structure; The hydrophobic material layer conformally covers the surface of the nanoparticle layer.

[0006] In some embodiments, the depth of the recessed unit does not exceed one quarter of the thickness of the metal base layer; and / or the depth of the recessed unit ranges from 10 μm to 100 μm.

[0007] In some embodiments, the nanoparticle layer comprises nanoparticles, the material of the nanoparticles comprises at least one of elemental silicon, silicon oxide, silicon nitride, tungsten nitride, and zirconium nitride, and the particle size of the nanoparticles ranges from 50 nm to 1000 nm.

[0008] In some embodiments, the nanoparticles have a projection area coverage of 20% to 90% on the surface of the concavo-convex texture structure along the vertical direction.

[0009] In some embodiments, the thickness of the nanoparticle layer is in the range of 0.05 μm to 2 μm; and / or the thickness of the hydrophobic material layer is in the range of 0.05 μm to 5 μm.

[0010] In some embodiments, the hydrophobic material layer is made of at least one of an organic silicon polymer, a fluoropolymer, and a ceramic.

[0011] In some embodiments, the material of the metal base layer includes at least one of iron, stainless steel, aluminum, copper, and titanium; and / or the metal base layer includes a multi-layer structure.

[0012] In some embodiments, the concave-convex texture structure includes a micron structure distributed on the surface of the metal base layer; the nanoparticle layer covers at least a portion of the micron structure to form a micro-nano structure; wherein polar covalent bonds are formed between the hydrophobic material layer and the micro-nano structure.

[0013] On the other hand, an embodiment of the present application further provides a method for preparing a metal cooking utensil, comprising the following steps: A concave-convex texture structure in the form of bionic leaf veins is formed on the surface of the metal substrate by one of embossing, etching, laser or roughening processes; Depositing a nanoparticle layer on the surface of the concavo-convex texture structure; A hydrophobic material layer is deposited on the surface of the nanoparticle layer by spraying, dipping or evaporation coating.

[0014] In some embodiments, in the step of depositing a nanoparticle layer on the surface of the concavo-convex texture structure, the deposition conditions include: vacuum degree 0.01Pa-0.2Pa, substrate bias 150V-600V; target current 70-90A, temperature 100-200°C.

[0015] In summary, the present application provides a metal cooking utensil, in which an irregular concave-convex texture structure in the form of bionic leaf veins is arranged on the inner surface of the metal base layer, and the synergistic effect of the nanoparticle layer and the hydrophobic material layer is combined to reduce linear wear through irregularly distributed rib units, wherein the irregular distribution means that the planar projection shapes of any two adjacent rib units in the vertical direction of the metal base layer surface are different; at the same time, the nanostructure of the nanoparticle layer and the concave-convex texture structure surface of the nanoparticle layer are combined to form a micro-nano structure to enhance hydrophobicity, which has the advantages of improving surface hydrophobicity to enhance anti-stick performance and extend the service life of the texture structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0017] Figure 1 is a schematic diagram of the hierarchical structure of metal cooking utensils according to some embodiments of the present application; Figure 2 is a partial schematic diagram of the surface of the concave-convex texture structure of some embodiments of the present application; Figure 3 is a partial schematic cross-sectional view of the concave-convex texture structure of some embodiments of the present application; 10-metal matrix layer; 20-nanoparticle layer; 30-hydrophobic material layer. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0019] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0020] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0021] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0022] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0023] The development of non-stick cooking utensils relies on coating technology and metal material innovation. In recent years, the use of pure metal materials such as stainless steel and titanium alloys to manufacture "zero-coating" cookware has become a trend. These materials are popular in the market due to their health benefits, durability, corrosion resistance, and lack of the risk of chemical coating peeling. However, the inherent high surface energy of metal materials results in poor hydrophobicity, which can easily cause food to stick during cooking (such as rice sticking to the pan, cooking frying pans burning), as well as discoloration due to high temperatures.

[0024] To improve the anti-stick properties of pure metal cookware, the current mainstream approach is to create a matrix of concave and convex dot patterns or textures on the cookware surface through mechanical stamping, etching, or laser processing. This structure aims to use the pits to retain water or oil, forming an isolation layer, supporting the food and reducing its contact area with the metal substrate, thereby achieving a certain anti-stick effect. However, the directional arrangement of this structure is prone to linear scratches under mechanical friction, causing the texture to quickly wear out and fail, and the anti-stick performance decreases significantly with repeated use.

[0025] Based on this, the present application proposes a metal cooking utensil, such as Figure 1 As shown, it comprises a metal base layer, a nanoparticle layer, and a hydrophobic material layer. The metal base layer is provided with a concave-convex texture structure in the form of bionic leaf veins. The concave-convex texture structure comprises a plurality of rib units and concave units formed between the rib units. The planar projection shapes of any two adjacent rib units in the direction perpendicular to the surface of the metal base layer are different. The nanoparticle layer is conformally coated on the surface of the concave-convex texture. The hydrophobic material layer is coated on the surface of the nanoparticle layer.

[0026] like Figure 2As shown, the bionic leaf vein-like concave-convex texture structure refers to a three-dimensional structure that simulates the branching morphology of plant leaf veins. It can be achieved through embossing or laser processing. "The planar projection shapes of any two adjacent rib units in the vertical direction are different" means that when viewed from a direction perpendicular to the cookware surface, the contours of any two adjacent rib units on a two-dimensional plane do not repeat. The vertical direction refers to the normal direction along any point on the cookware surface. In three-dimensional geometry, a normal is a straight line tangent to and perpendicular to a given curve or surface. For example, rib A may have a forked tree branch-like contour; adjacent rib B may have an earthworm-like contour; and adjacent rib C may have an irregular polygonal island-like contour. Thus, the shape and spatial arrangement of the rib units exhibit a three-dimensional, irregular distribution. This arrangement breaks the regularity of traditional matrix textures (such as dot patterns, parallel stripes, or other regular spacing and sizes), forming a disordered network structure similar to plant leaf veins, which effectively distributes mechanical stress on the cookware surface. This "biomimetic vein-like concave-convex texture" mimics the vein network of a plant leaf. It not only mimics the two-dimensional pattern of veins, but more importantly, the three-dimensional, undulating structure created by their influence on the mesophyll tissue in three dimensions. The raised areas correspond to the veins (which serve as a supporting skeleton), while the recessed areas correspond to the mesophyll areas between them. The resulting three-dimensional microstructured surface has a specific spatial distribution pattern, such as dendritic, reticular, or hierarchical.

[0027] Specifically, in the concave-convex texture structure of the bionic leaf vein morphology, the concave units formed between the convex rib units include a plurality of interconnected grooves, which extend along irregular paths and have a forked structure; wherein, the planar projection shapes of any two adjacent convex rib units in the vertical direction are different from each other, and there are interconnected forked grooves between adjacent convex rib units, so that a water vapor channel is formed on the inner surface of the groove on the surface of the cookware.

[0028] In some embodiments, such as when the inner pot of a cooking utensil is used in a rice cooking scenario, a large amount of water vapor generated by the boiling heat in the pot will gather in the upper area, and under external cooling conditions, it will condense into water along the side wall of the pot and flow downward. However, the existing general smooth surface or the inner pot surface with independent groove texture will be blocked by the expanded rice, and the water cannot flow evenly along the inner wall to the fully heated bottom. The rice at the bottom often becomes dry and hard, while the rice on the upper side and surface is soft and rotten, affecting the taste of the rice.

[0029] In this embodiment, irregularly distributed bifurcated grooves form interconnected vapor channels, dividing the cookware surface into adjacent rib units of varying shapes. These interconnected vapor channels establish multi-directional vapor transmission pathways on the cookware's inner surface, effectively guiding the flow of vapor during cooking while reducing the possibility of blockage, thereby improving heating uniformity and moisture distribution.

[0030] Irregular path extension means that the direction of the groove simulates the natural diffusion trajectory of the liquid, so that the rib units formed present an irregular distribution shape like the branching of plant leaf veins. The water vapor channels formed by the grooves can form a water vapor connection network with a capillary effect, guiding the condensed water on the top to penetrate to the bottom of the pot. The bifurcated structure allows the water flow to choose an alternative path when encountering local resistance, avoiding the interruption of diversion caused by the blockage of a single groove. The curved edges of the rib units can reduce linear contact with the rice and reduce the probability of adhesion. When water vapor condenses on the side wall, the irregular groove network provides multi-directional flow options, automatically adjusting the water flow distribution according to the temperature difference, so that the water supply at the bottom and sides reaches a dynamic balance.

[0031] Compared to existing technologies, traditional solutions use independent linear grooves or smooth surfaces, resulting in a single water flow path that is easily clogged. The grooves in this embodiment form a biomimetic water vapor network, establishing redundant diversion paths. Their bifurcated structure enhances inter-regional moisture distribution. Combined with the differently shaped ribs, they increase the heating surface area while reducing surface adhesion, achieving more efficient dynamic moisture balance and improving the non-stick properties and wear resistance of the cookware's inner surface.

[0032] Furthermore, the depth of the groove increases gradually along the side areas of the inner surface of the pot, the arc transition area, and the bottom area, and / or the width of the groove decreases gradually along the side areas of the inner surface, the arc transition area, and the bottom area, to guide the water flow on the inner surface of the pot to flow in a dispersed manner. Preferably, the depth of the groove ranges from 10μm to 100μm, and the width of the groove ranges from 0.01mm to 4mm. The size of the groove is set according to the shape of the pot and should meet the following conditions: the average depth of the grooves in the side areas ≤ the average depth of the grooves in the arc transition area ≤ the average depth of the grooves in the bottom area, or the average width of the grooves in the side areas ≥ the average width of the grooves in the arc transition area ≥ the average width of the grooves in the bottom area.

[0033] The groove depth refers to the vertical distance between the bottom of the groove and the inner surface of the inner pot. The average groove depth is the arithmetic mean of the values ​​measured at different locations along the groove's length. The side area refers to the entire vertical or nearly vertical cylindrical wall of the inner pot, from the bottom to the pot opening. This can be formed using a stamping process to create a continuous curved surface structure. Its shallow groove structure helps control water flow and prevent excessive evaporation. The arc transition area refers to the transition surface connecting the side and bottom. A gradually changing curvature can be formed using a spinning process. Medium-depth grooves maintain water flow continuity. The bottom area refers to the flat or spherical area at the bottom of the inner pot that directly contacts the heating unit. The deepest grooves are formed using a laser etching process to collect and store condensed water flowing there. A gradient distribution indicates that the groove depth varies spatially. Depth variation can be achieved through segmented processing or parametric molds.

[0034] When condensation occurs on the surface of the inner pot, the shallower grooves in the side areas preferentially guide the water flow to form a thin liquid film, which flows downward under the action of gravity. When the water flows through the arc transition area, the medium-depth grooves maintain flow continuity through capillary action to prevent the liquid film from breaking. After reaching the bottom area, the deepest grooves form a water storage space, allowing the water to fully evaporate in the high-temperature area. This depth gradient change not only avoids insufficient water retention time due to excessively deep grooves in the side areas, but also prevents flow resistance in the bottom area due to excessively shallow grooves, thereby achieving orderly migration of water from the upper part to the heating area. By establishing a depth gradient relationship, this solution matches the groove structure with the thermodynamic conditions of each area, forming a water vapor channel that conforms to the laws of fluid dynamics.

[0035] Specifically, the average depth h1 of the grooves in the side area refers to the average depth of the grooves in the side area of ​​the inner pot, which can be achieved through laser engraving or chemical etching processes. It is used to form a preliminary condensation water convergence path on the side wall, while avoiding rice sticking or structural strength reduction due to excessive depth. The average depth h2 of the grooves in the arc transition area refers to the average depth of the grooves in the transition area between the side wall and the bottom of the inner pot. It can be achieved by using gradual processing parameters to enhance the water flow guidance ability of the curved surface area and prevent water vapor retention. The average depth h3 of the grooves in the bottom area refers to the average depth of the grooves in the bottom area of ​​the inner pot. It can be achieved by controlling the processing depth in different areas to accelerate the transport of water to the high-temperature area. At the same time, by limiting the ratio of h3 to h1 to no more than 1.5 times, it prevents excessive depth differences from causing capillary force imbalance.

[0036] The increasing gradient of groove depth creates a continuous flow path from the sidewalls to the bottom of the pot. Shallow grooves on the side allow condensed water to initially converge on the sidewalls without affecting the moisture content of the rice. The transition depth of the arc transition area accelerates the water flow in the curved area, while the greater depth at the bottom promotes contact between water and the high-temperature area. The strictly defined depth ratios of each zone promote a gradual increase in capillary force while avoiding sudden changes in depth that could disrupt the water flow or weaken the structure.

[0037] This solution achieves dynamic water flow balance through regionalized depth gradients and upper limit constraints, enabling precise control of water conduction capacity in different areas of the inner pot. This further reduces the difference in moisture content between the bottom and sidewalls of the rice, resulting in a more uniform rice texture. Furthermore, limiting the depth ratio avoids problems such as flow disturbances or decreased structural strength caused by excessive depth in certain areas, thereby improving the long-term reliability of the inner pot.

[0038] Furthermore, in this embodiment, the groove width is defined as follows: When a fluid flows through a complex channel, a certain channel region has flow characteristics equivalent to a circular pipe, and the diameter of this hypothetical circular pipe is the groove width. A gradient-decreasing groove width distribution refers to a gradual decrease in groove width as it extends from the side regions toward the bottom region. This can be achieved by designing the groove in a stepped width during mold processing or by adjusting the tool path section by section using a CNC engraving process. This distribution accommodates differences in fluid flow characteristics by adjusting the width ratios of different regions.

[0039] Specifically, the groove width in the bottom area is set to the minimum value, the groove width in the arc transition area is slightly larger than that in the bottom area, and the groove width in the side area is the largest, forming a drainage acceleration zone. During the flow of condensed water, the change in width gradient leads to differences in fluid pressure distribution, driving the water flow to converge from the side area to the bottom area. The decreasing width distribution of the grooves further enhances fluid mixing through the turbulent effect, avoids local retention, and optimizes the flow path to reduce resistance. Therefore, by setting a gradient change in the water vapor channel (depth and / or width of the groove) on the inner surface of the cookware to achieve better water vapor fluidity and further improve the non-stick performance, the synergistic effect of the bionic texture of the metal matrix layer and the nanoparticle layer and the hydrophobic material layer achieves a long-lasting anti-stick effect.

[0040] A nanoparticle layer is a coating of nanoscale particles formed by physical or chemical vapor deposition. It can be made of silicon-based or nitride materials, and its rough surface enhances the adhesion of hydrophobic materials. A hydrophobic material layer is a polymer coating with low surface energy, deposited through chemical vapor deposition to form a continuous layer that effectively reduces surface wettability.

[0041] Specifically, the bionic texture of the metal matrix layer forms a multi-directional support structure through irregular rib units. When subjected to external forces, the irregular ribs disperse stress and avoid directional scratches. The recessed units and rib units form a liquid storage space, which stores the oil film during the cooking process to form an isolation layer. The nanoparticle layer forms nano-scale protrusions on the basis of the micron-scale texture, increasing the specific surface area and making the hydrophobic material more firmly bonded. The hydrophobic material layer reduces the surface energy, causing the liquid to form a high contact angle and roll off quickly. The three work together to form a multi-level composite structure with macro-support, micro-liquid storage, and nano-roughness.

[0042] Compared to existing technologies, existing solutions employ a regularly arranged micron-scale lattice structure, which is susceptible to scratches along the arrangement direction under friction, thus compromising the texture's integrity. The irregular vein texture of this solution lacks a fixed directionality, dispersing external forces across the shaped veins, significantly improving scratch resistance. The composite coating of a nanoparticle layer and a hydrophobic material further reduces surface energy on top of this micron-structured structure, creating a more stable superhydrophobic interface.

[0043] Through the above technical solution, this application reduces the wettability of the metal surface, allowing the oil film to stably cover the textured liquid storage space, significantly reducing direct contact between food and the metal substrate. The irregularly distributed rib structure provides multi-directional support to resist linear damage caused by friction with utensils, extending the service life of the texture structure. The synergistic effect of the nano-rough surface and the low surface energy coating achieves a long-lasting anti-stick effect.

[0044] In some embodiments, the depth of the recessed units on the inner surface of the metal base layer does not exceed one quarter of the thickness of the metal base layer.

[0045] Among them, Figure 3 As shown in Figure 1, the depth of a recessed unit is the vertical distance from the top to the bottom of the rib in a concave-convex texture. This can be achieved by controlling the penetration through etching or embossing. This parameter is directly related to the mechanical integrity of the metal matrix. Shallower recesses can prevent structural weakening caused by stress concentration.

[0046] The metal matrix thickness refers to the remaining material thickness of the substrate in the area where the recessed units are located. This can be achieved by selecting the initial sheet thickness and combining it with the surface machining allowance. By defining the ratio of the recess depth to the matrix thickness, the metal matrix retains sufficient deformation resistance after processing.

[0047] Specifically, the depth of the recessed units forms a constrained relationship with the thickness of the metal matrix layer. By controlling the recessed depth to within a quarter of the matrix thickness, the metal matrix retains sufficient mechanical strength after texture processing. During the cooking process, when the metal matrix is ​​subjected to external mechanical friction or thermal stress, the shallower recessed units will not significantly weaken the matrix structure, thereby preventing the texture structure from failing due to deformation or damage to the matrix. At the same time, the retained depth of the recessed units can still form a liquid storage space, maintaining the continuity of the oil or water film through capillary action, and achieving dynamic isolation between the food and the metal surface.

[0048] If the depth of the depression often exceeds one-third of the substrate thickness, the material in some areas of the substrate is too thin. Repeated friction with the spatula can easily cause cracks to propagate at the edges of these deep depressions, ultimately leading to overall delamination of the texture. This solution, by establishing a control mechanism that correlates depth with substrate thickness, further improves the texture's damage resistance while retaining its liquid storage function.

[0049] Through the above technical solution, this application further solves the problem of reduced mechanical strength of metal substrate surface textures caused by excessively deep depressions, avoiding texture failure caused by cracking in weak areas of the substrate. Furthermore, the proper control of the depression depth ensures that the liquid storage space remains stable even under high-temperature cooking conditions, extending the duration of the anti-stick effect.

[0050] In some embodiments, the depth of the recessed units ranges from 10 μm to 100 μm. A recessed depth that is too small will result in insufficient liquid storage, making it difficult to form a good isolation layer. A recessed depth that is too large will weaken the structural strength of the metal matrix. Specifically, when the depth is controlled within the range of 10 to 100 μm, the recessed units can both reduce contact between food and the metal matrix by storing liquid to form an isolation layer, while also avoiding local stress concentration in the metal matrix or a decrease in overall mechanical strength due to excessive depth.

[0051] In some optional embodiments, the depth of the recessed units ranges from 30 μm to 60 μm. When the depth is controlled within this range, the recessed units can further stably store the oil film or water film during the cooking process, while the metal substrate can maintain its structural integrity when subjected to spatula friction or high-temperature thermal stress, further preventing scratches from expanding or texture collapse.

[0052] Compared to existing technologies, these recessed units typically utilize a uniformly distributed micron-scale dimple structure. Their depth is determined solely based on anti-sticking requirements, without considering the compatibility of the metal substrate's mechanical properties. This results in the dimples being easily scratched or crushed in actual use. This solution, by limiting the depth range, achieves a synergistic optimization between the liquid storage function and structural strength of the recessed units.

[0053] Through the above technical solution, the present application achieves the stable maintenance of the liquid isolation layer during the cooking process, while avoiding the problem of decreased substrate strength caused by excessively deep depressions, so that the metal substrate can further maintain the integrity of the texture structure and the durability of the anti-stick performance under repeated friction and high temperature environment.

[0054] In some embodiments, the nanoparticle layer comprises nanoparticles, the material of the nanoparticles comprises at least one of elemental silicon, silicon oxide, silicon nitride, tungsten nitride, and zirconium nitride, and the particle size of the nanoparticles ranges from 50 nm to 1000 nm.

[0055] Among them, the nanoparticle layer refers to a composite structure layer formed on the surface of a metal substrate by a physical or chemical deposition process. Specifically, it can be achieved by magnetron sputtering or plasma-enhanced chemical vapor deposition. Its function is to construct a composite interface of micron-scale concave-convex structure and nano-scale roughness. Among them, elemental silicon and silicon oxide materials have high hardness characteristics and can resist scratch damage by increasing the mechanical strength of the surface. For example, amorphous silicon particles are deposited by radio frequency magnetron sputtering. Among them, tungsten nitride and zirconium nitride materials have high chemical inertness. Specifically, they can be synthesized by reactive magnetron sputtering in a nitrogen environment. Their function is to inhibit oxidative corrosion in high-temperature cooking environments. Among them, the particle size range of 50nm-1000nm can form a synergistic effect with the micron-scale substrate concave-convex structure. Specifically, it can be achieved by adjusting the target power and gas flow during the deposition process. Its function is to balance the dispersion and packing density of the nanoparticles to avoid agglomeration caused by too small particle size or structural collapse caused by too large particle size.

[0056] Specifically, by controlling the material composition and particle size distribution of the nanoparticles, a uniformly covered nanoscale rough layer is formed on the surface of the micron-scale concave-convex texture. Elemental silicon or silicon nitride particles form anchor nodes on the substrate surface, enhancing the bonding strength of subsequent hydrophobic material layers through a mechanical interlocking effect. Particles with a particle size range of 50nm-1000nm form submicron-scale secondary protrusions, which collaborate with the micron-scale recessed units of the substrate to construct a multi-level composite structure, increasing the interfacial energy barrier of the solid-liquid contact surface. Tungsten nitride particles improve the surface wear resistance through their high hardness characteristics, and preferentially bear shear stress during the spatula friction process, thereby protecting the substrate texture structure from damage.

[0057] In some embodiments, the particle size of the nanoparticles ranges from 100 nm to 500 nm, which further facilitates the formation of micro-nano rough surfaces and enhances hydrophobicity.

[0058] Compared to existing technologies, traditional approaches rely solely on a single-scale, micron-scale concave-convex structure. This surface roughness is insufficient to form a stable gas-liquid interface, and its limited mechanical strength makes it prone to linear scratches. This approach introduces a nanoparticle layer to create a micro-nano composite structure. While maintaining the liquid reservoir function, it utilizes nanoscale secondary roughness to enhance surface hydrophobicity. The hard nanoparticles act as a physical barrier to disperse external loads, further blocking the path of scratches extending across the substrate.

[0059] Through the above technical solution, this application can significantly improve the surface hydrophobicity without destroying the micron-scale liquid storage structure, reducing the direct contact area between the food and the metal substrate during cooking. The nanoparticle layer acts as a transition layer to enhance the interfacial bonding strength and reduce the risk of delamination of the hydrophobic material due to differences in thermal expansion coefficients. The introduction of hard particles makes the surface resistant to plastic deformation, maintaining the integrity of the multi-level roughness structure after long-term use, thereby prolonging the maintenance of anti-stick properties.

[0060] In some embodiments, the projection area coverage of the nanoparticles on the surface of the concavo-convex texture structure along the vertical direction is 20%-90%.

[0061] Projected area coverage refers to the proportion of area covered by nanoparticles per unit area. This can be controlled using magnetron sputtering or vapor deposition processes by adjusting parameters such as deposition time, target power, or substrate bias voltage. This feature, by controlling the distribution density of nanoparticles, achieves gap-filling effects in micron-scale concave and convex structures while preventing excessive deposition and resulting particle stacking.

[0062] Specifically, the coverage of nanoparticles on the concave-convex textured surface is limited to a specific range. If the coverage is insufficient, the nanoparticles cannot effectively fill the gaps formed by the micron-sized structures, resulting in insufficient reduction in surface energy. If the coverage is too high, the particles will accumulate and block the liquid storage function of the micron-sized concave units, while also weakening the anti-friction performance of the matrix structure. By controlling the coverage rate between 20% and 90%, the nanoparticles can form localized hydrophobic areas while retaining the liquid storage space of the concave units.

[0063] In some embodiments, the projected area coverage of the nanoparticles on the surface of the concavo-convex texture structure is 50%-80%.

[0064] The preferred coverage range of 50%-80% is achieved by optimizing process parameters to uniformly distribute the nanoparticles across the concave-convex surface. This can be achieved through segmented deposition or dynamic scanning deposition. This range balances hydrophobicity and structural stability, enhancing the synergistic effect between the nanoparticle layer and the microstructure while maintaining the mechanical support of the substrate texture.

[0065] At the optimal concentration of 50%-80%, the particle distribution density reaches a critical state, forming a continuous hydrophobic layer covering the surface of the micron-sized ridge units while avoiding completely blocking the recessed units. This range has been experimentally verified to maintain the bonding strength between the particle layer and the substrate during dynamic friction.

[0066] If metal cooking utensils are typically coated with nanoparticles uniformly across the entire surface, resulting in a coverage rate close to 100%, this can over-cover the micron-scale concave-convex texture, potentially rendering it incapable of storing liquid. However, this solution, by limiting the coverage rate, preserves the liquid storage capacity of the microstructure while also reducing the surface energy through the hydrophobic properties of the nanoparticles, creating a dual anti-sticking mechanism. The prior art does not disclose any technical means for achieving synergistic effects of micro- and nanostructures through coverage control.

[0067] Through the above-mentioned technical solution, this application solves the problems of fluctuating hydrophobic properties and reduced structural strength caused by insufficient or excessive nanoparticle coverage. During the cooking process, the synergistic effect of the nanoparticle layer and the micron-scale recessed liquid storage structure forms a stable gas-liquid isolation layer, reducing direct contact between the food and the metal substrate. Furthermore, moderate nanoparticle coverage avoids interlaminar stress caused by excessive deposition, further improving the substrate's resistance to wear and tear due to friction.

[0068] In some embodiments, the thickness of the nanoparticle layer ranges from 0.05 μm to 2 μm.

[0069] The nanoparticle layer increases surface roughness and provides a base for hydrophobic materials to adhere to. The thickness range refers to the dimension of the nanoparticle layer perpendicular to the substrate surface. This can be controlled by adjusting deposition time or process parameters. Selecting this range balances coverage continuity and structural stability.

[0070] When the nanoparticle layer is within this thickness range, it forms a uniform and continuous surface coverage, avoiding local exposure due to being too thin or stress concentration due to being too thick. When the cooking utensils experience temperature changes or mechanical friction, the particle layer at this thickness can better buffer the external forces and prevent interlayer delamination due to insufficient bonding between particles. At the same time, this thickness range also provides a more suitable three-dimensional surface roughness, providing better support for the subsequent construction of the microstructure of the hydrophobic material layer.

[0071] By limiting the thickness to a specific range, this solution allows the particle layer to maintain interfacial bonding stability despite differences in thermal expansion coefficients at high temperatures, overcoming the low wear resistance inherent in conventional structures due to inappropriate thickness. Through this technical solution, the present application achieves reliable bonding of the nanoparticle layer to the substrate structure even in high-temperature cooking environments, further preventing surface defects caused by particle shedding while maintaining a stable surface roughness, providing structural support for the long-term preservation of hydrophobic properties.

[0072] In some embodiments, the hydrophobic material layer has a thickness ranging from 0.05 μm to 5 μm.

[0073] The thickness of the hydrophobic material layer refers to the vertical dimension of the organic or inorganic material covering the surface of the nanoparticle layer. This can be achieved using plasma-enhanced chemical vapor deposition, spray coating, or spin coating. This thickness range ensures hydrophobicity while avoiding internal stress concentration caused by material accumulation. The continuous coverage of the hydrophobic material layer refers to the complete microscopic coverage of the undulating structure of the nanoparticle layer surface. This can be achieved by adjusting the deposition rate or solution concentration to avoid local uncovered areas that increase surface energy.

[0074] The thickness of the hydrophobic material layer is set to be above 0.05μm, which helps to cover the surface protrusions of the nanoparticle layer, thereby forming a continuous interface layer with low surface energy. When the thickness is controlled within 5μm, it helps to alleviate the problem of interfacial cracking caused by differences in thermal expansion coefficients between layers. If the hydrophobic layer is too thick, cracks may appear under high-temperature thermal shock conditions; if the coating is too thin, it will be difficult to fully cover the microstructure of the substrate, thereby affecting the stability of the hydrophobic performance. By limiting the thickness range of the hydrophobic material layer, it can adapt to the three-dimensional morphology of the substrate while achieving a balance between mechanical strength and interfacial stress distribution.

[0075] In some embodiments, the thickness of the hydrophobic material layer ranges from 0.5 μm to 2 μm. By further limiting the thickness of the hydrophobic material layer, the balance between the mechanical strength of the hydrophobic material layer and the interfacial stress distribution is further improved.

[0076] Through the above technical solution, the present application can form a stable low-surface-energy interface, reducing direct contact between food and the metal substrate during cooking. A hydrophobic material layer within this thickness range can withstand repeated scraping, preventing degradation of anti-stick properties due to mechanical damage, while also preventing coating peeling due to thermal cycling, further extending the life of the cooking utensil.

[0077] In some embodiments, the hydrophobic material layer comprises at least one of an organosilicon polymer, a fluoropolymer, and a ceramic.

[0078] Among them, silicone polymer refers to a polymer compound containing a silicon-oxygen bond main chain, which can be specifically realized by polydimethylsiloxane or silicone rubber. Through the flexibility and low surface energy characteristics of its molecular chain, a continuous covering film layer is formed on the surface of the nanoparticle layer. Fluoropolymer refers to a synthetic polymer material containing fluorine atoms in the main chain or side chain, which can be specifically realized by polytetrafluoroethylene or fluorinated ethylene propylene copolymer, and the strong electronegativity of fluorine atoms is used to reduce the surface energy of the material. Ceramics refer to inorganic non-metallic materials formed by high-temperature sintering, which can be specifically realized by aluminum oxide or silicon carbide ceramic coatings, and the surface's tolerance to mechanical friction is enhanced by high hardness and thermal stability.

[0079] Silicone polymers, through the flexibility of their molecular chains, form a uniform coating on the surface of the nanoparticle layer, reducing the occurrence of surface microcracks. Fluoropolymers, through the directional arrangement of fluorine atoms at the interface, create a low-adhesion surface. Ceramic materials, through the densification of their crystal structure, enhance the stability of the texture at high temperatures. These three types of materials can be used alone or in combination to form multilayer composite structures, reducing surface energy while improving scratch resistance.

[0080] Through the above technical solution, the surface of metal cooking utensils has better low surface energy characteristics, further improving the anti-stick effect, and the service life of the texture structure can be further increased, which can reduce the impact of mechanical scratches on the anti-stick performance to a certain extent.

[0081] In some embodiments, the material of the metal base layer includes at least one of iron, stainless steel, aluminum, copper, and titanium.

[0082] The metal matrix layer refers to the metal material layer that forms the main structure of the cooking utensil. It can be made of one or more combinations of iron, stainless steel, aluminum, copper, or titanium. Iron is alloyed to improve corrosion resistance, stainless steel uses chromium to form a passivation film to enhance structural strength, aluminum is pre-anodized to improve surface adhesion, copper is treated with an anti-oxidation process to inhibit oxidation, and titanium is plasma activated to improve deposition.

[0083] In some specific embodiments, the materials used may include metals such as iron, stainless steel, aluminum, copper, and titanium.

[0084] In some embodiments, the metal base layer comprises a multi-layer structure, i.e., a multi-layer metal composite structure, such as a steel-aluminum-steel three-layer composite, a steel-aluminum two-layer composite, or a steel-aluminum-titanium composite inner pot structure. These materials or composite structures can be selected and applied according to actual needs.

[0085] In some embodiments, the concave-convex texture structure includes a microstructure distributed on the surface of the metal base layer; the nanoparticle layer covers at least a portion of the microstructure to form a micro-nanostructure; wherein polar covalent bonds are formed between the hydrophobic material layer and the micro-nanostructure.

[0086] Specifically, when the nanoparticle layer includes a nano-silicon crystal layer, its silicon nanoparticles are randomly scattered on the bionic leaf vein texture surface with a micron-scale rough structure (the concave-convex texture structure on the surface of the metal base layer) to form a rough surface with micron-nano structures that are interlocked with each other, further improving the hydrophobic properties of the original concave-convex texture surface. In addition, the silicon crystal layer can "take root" on the surface of the metal base layer, providing an anchor point for the strong bonding between the metal base layer and the low surface energy hydrophobic material layer (especially the ceramic layer or the silicon-oxygen bond material layer).

[0087] Specifically, when the hydrophobic material layer includes a silicon-oxygen layer, "polar covalent bonds" refer to silicon-oxygen bonds, in which silicon atoms (electronegativity 1.90) and oxygen atoms (electronegativity 3.44) are bonded by a shared electron pair, but the electrons are biased toward the oxygen atoms, forming polarity. The silicon-oxygen bonds in the silicon crystal layer form a three-dimensional network structure, forming a stable covalent crystal, which can enhance the hardness, scratch resistance, corrosion resistance, and thermal stability of the cookware surface coating.

[0088] Among them, the nanoparticle layer provides a skeleton structure of silicon atoms for the hydrophobic material layer, forming silicon-oxygen bonds with the hydrophobic material layer for strong bonding.

[0089] Fluorine-containing / silicon-containing low surface energy polymers are deposited on the surface of the micro-nano structure by spraying, dipping or evaporation coating, combining with the original silicon crystal anchor particles on the surface. During the heating process, a crystal catalytic reaction occurs, which improves the surface performance of the cookware and ultimately achieves extremely strong bonding force and non-stick properties.

[0090] On the other hand, an embodiment of the present application further provides a method for preparing a metal cooking utensil, comprising the following steps: A concave-convex texture structure in the form of bionic leaf veins is formed on the surface of the metal substrate by one of embossing, etching, laser or roughening processes; Deposition on the surface of the concave-convex texture structure to form a nanoparticle layer; A hydrophobic material layer is deposited on the surface of the nanoparticle layer by spraying, dipping or evaporation coating.

[0091] The bionic leaf vein-like concave-convex texture structure simulates the irregular branching of plant veins, creating interlaced convex and concave elements on the metal surface. Its spatial distribution is multidirectional. Specifically, this can be achieved by pre-engraving the vein pattern with a mold in the embossing process, or by adjusting laser parameters to create a fractal path. This breaks the single directionality of the traditional matrix arrangement and thus disperses frictional stress.

[0092] Deposition of the nanoparticle layer involves forming a micro-nano composite structure composed of silicon-based or nitride materials on a textured surface through physical vapor deposition, chemical vapor deposition, or electroplating. Magnetron sputtering can be used to control particle size and coverage, leveraging the rough surface of the nanoparticles to increase the surface area for hydrophobic material attachment while preventing excessive particle accumulation that could bury the textured structure.

[0093] Deposition of the hydrophobic material involves forming a continuous, low-surface-energy coating on the nanoparticle layer through spraying or vapor deposition. Silicone prepolymers can be cross-linked and cured under vacuum conditions, allowing the hydrophobic material to tightly fill the gaps between the nanoparticles, forming a mechanically interlocking structure that reduces interfacial energy and prevents oil film rupture.

[0094] Specifically, during the metal substrate processing stage, by combining embossing and laser micro-engraving processes, the macroscopic leaf vein outline is first formed, and then the depth of the local depressions is refined, so that the texture has both biomimetic morphology and mechanical strength. Subsequently, in a vacuum environment, by adjusting the substrate bias and target current, the nanoparticles are controlled to be deposited on the textured surface at an oblique incidence, forming a gradient-distributed rough layer. Finally, a fluoropolymer solution is sprayed under low temperature conditions, and the hydrophobic material is allowed to penetrate into the gaps between the nanoparticles by capillary action. After curing, a protective layer that is conformal to the texture is formed. "Conformal" means that the coating or film completely adheres to the shape of the substrate (here, the textured surface). This process sequence ensures that each functional layer is constructed in sequence, avoiding subsequent high-temperature treatment that damages the existing structure.

[0095] The multi-directional branching structure of this bionic leaf vein texture disperses frictional stress across ribs in different directions, reducing the risk of linear damage. Furthermore, this solution increases the interfacial bonding area through a nanoparticle layer, extending the bond between the hydrophobic material and the substrate from a two-dimensional plane to a three-dimensional anchor, significantly improving the coating's durability.

[0096] Through the above technical solution, this application solves the problems of poor scratch resistance on the surface of pure metal cooking utensils due to the obvious directionality of the microstructure, as well as the reduced anti-stick performance caused by the easy peeling of the hydrophobic layer. The bionic leaf vein texture disperses friction stress through multi-directional ribs, reducing the occurrence of linear scratches; the gradient deposition of the nanoparticle layer and the hydrophobic material forms a mechanical interlocking interface, preventing the coating from delaminating and falling off during use. As a result, the hydrophobic properties of the metal substrate surface are maintained over a long period of time, reducing the probability of direct contact between food and metal, thereby extending the anti-stick life of the cooking utensils.

[0097] In some embodiments, in the step of depositing a nanoparticle layer on the surface of the concavo-convex texture structure, the deposition conditions include: vacuum degree 0.01Pa-0.2Pa, substrate bias 150V-600V; target current 70-90A, temperature 100-200°C.

[0098] Specifically, taking the process of forming silicon-based nanoparticles on the surface of the metal texture layer as an example, the process includes the following steps: (1) Matrix ion cleaning: maintain a vacuum of 0.01Pa-0.1Pa in an inert gas atmosphere (such as argon or helium), apply a substrate bias of 500V-800V and a duty cycle of 60%-80% for plasma bombardment to remove surface contaminants and activate the metal matrix.

[0099] (2) Silicon-based particle deposition: magnetron sputtering or chemical vapor deposition is used. A vacuum of 0.1Pa-0.5Pa is maintained in an inert gas environment. By adjusting the substrate bias voltage of 100V-200V and the target current of 70A-90A, silicon-based particles with a particle size of 50-1000nm are generated at a substrate temperature of 100-250℃. The layer thickness is controlled in the range of 0.05μm-2μm.

[0100] (3) In situ surface functionalization: nitrogen, oxygen or carbon source gas is introduced and plasma bombarded under a vacuum of 0.1Pa-0.3Pa to convert the surface particles into functional compounds such as silicon nitride, silicon oxide or silicon carbide.

[0101] The following describes the details in conjunction with specific embodiments.

[0102] Example 1 This embodiment provides a metal cooking utensil, the metal base layer of which is a 304-Al-430 three-layer composite inner pot, and the preparation steps are as follows: (1) Bionic leaf vein texture processing: The inner surface of the metal substrate layer (304 stainless steel surface) is embossed to form a bionic leaf vein concave-convex texture structure. The convex rib units are irregularly distributed and have different projection shapes. The depth of the concave units is 40 μm. The surface is mechanically sanded. (2) Nanoparticle layer deposition: Ion cleaning: argon atmosphere, vacuum degree 0.01 Pa, Ar gas flow rate 200 sccm, substrate bias 600 V, duty cycle 70%, bombardment for 2 min; Silicon particle deposition: The silicon target was turned on, Ar gas maintained at a vacuum of 0.15 Pa, substrate bias voltage of 150 V, duty cycle of 60%, target current of 80 A, temperature of 150°C, and deposition time of 10 min. Elemental silicon particles with a particle size of approximately 400 nm were formed, irregularly covering the textured surface with a projected area coverage of 70% and a particle layer thickness of approximately 0.3 μm. Surface nitriding: nitrogen is introduced, the vacuum degree is 0.2Pa, and plasma bombardment is performed to form silicon nitride phase on the surface of silicon particles; (3) Deposition of hydrophobic material layer: spraying a silicone ceramic coating on the surface with a controlled thickness of 1.8 μm to form a hydrophobic material layer; wherein, the hydrophobic material layer and the nanoparticle layer form a micro-nano structure on the concave-convex texture surface.

[0103] Example 2 This embodiment provides a metal cooking utensil, which differs from the first embodiment in that: (1) Metal substrate layer: 304 stainless steel substrate, the inner surface is laser engraved to form a concave and convex texture of bionic leaf veins. The convex rib units are irregularly branched and have different projection shapes. The depth of the concave units is 50 μm.

[0104] (2) Nanoparticle layer: Elemental silicon particles were deposited on the textured surface by magnetron sputtering, with a particle size of 300 nm, a coverage of 80%, and a layer thickness of 0.8 μm. Process parameters: vacuum degree 0.1 Pa, bias voltage 200 V, target current 75 A, and temperature 150 °C. (3) Hydrophobic material layer: sprayed polytetrafluoroethylene, layer thickness 1.2 μm.

[0105] Example 3 This embodiment provides a metal cooking utensil, which differs from the embodiment 1 in that the coverage rate of the projected area of ​​the nanoparticles is 25%.

[0106] Example 4 This embodiment provides a metal cooking utensil, which differs from the first embodiment in that the particle size of the silicon nitride material in the nano-particle layer is 200 nm.

[0107] Example 5 This embodiment provides a metal cooking utensil, which differs from the first embodiment in that the hydrophobic material layer is replaced by an organic silicon polymer.

[0108] Example 6 This embodiment provides a metal cooking utensil, which differs from the first embodiment in that the surface of the silicon particles is not nitrided after deposition.

[0109] Comparative Example 1 The difference between this comparative example and Example 1 is that the hydrophobic material layer is directly sprayed on the textured surface without the nanoparticle layer.

[0110] Comparative Example 2 The difference between this comparative example and Example 1 is that the inner surface of the metal base layer is processed into regular matrix concave points (non-bionic leaf veins).

[0111] Comparative Example 3 The difference between this comparative example and Example 1 is that the inner surface of the metal base layer has no surface texture.

[0112] Performance Testing In order to verify the progress of the examples of the present application, the samples of the examples and comparative examples were tested as follows: 1. Non-stick cooking life test Test method: Take 2 cups of rice into each pot (for pots with silk-screen printing, 3 cups for 30-type and 5 cups for 40-type / 50-type), add appropriate amount of rice and water and cook according to normal cooking methods (use standard pot bottom temperature products and standard rice-to-water ratio). After cooking, keep warm for 10 minutes. Check the amount of rice remaining in the inner pot by turning the pot upside down and letting gravity or gently shaking the inner pot to see if all the rice falls out. Continue cooking until the rice drops below the second level non-stick level (judgment standard: rice weight ≤ 50g is second level non-stick).

[0113] Test results: as shown in Table 1.

[0114] Table 1

[0115] Test Results Analysis: The three comparative examples demonstrate that both the surface texture and the nanoparticle layer (silicon crystal layer) contribute to the longevity of the inner pot's non-stick performance. The surface texture primarily provides wear protection, while the silicon crystal layer enhances performance through a stronger bond. The hardened silicon crystal layer further enhances the surface's non-stick lifespan. The results of Comparative Examples 2 and 3 also demonstrate that the irregularly distributed, biomimetic, concave-convex texture structure exhibits superior non-stick performance compared to a regular matrix-distributed concave-convex texture structure. Therefore, the combined use of an irregularly distributed surface microstructure, a nanoparticle layer, and a hydrophobic material layer can achieve a more durable non-stick effect.

[0116] 2. Wear resistance test Test method: Use dishwashing liquid to prepare washing water with a concentration of 5%, 3M (7447C) scouring pad, load 2.5kgf, swing left and right as one stroke, replace the scouring pad every 250 strokes, check every 250 strokes whether the coating is exposed to the substrate (non-filled type: terminate the test when ≥10 lines are exposed; filled type: terminate the test when flaking occurs), and record the number of times the coating is exposed to the substrate.

[0117] Test results: as shown in Table 2.

[0118] Table 2

[0119] Analysis of test results: From the comparison between Example 1 and Comparative Example 3, it can be seen that the surface texture significantly improves the wear resistance, and the hard silicon crystal layer also plays a role in wear resistance and scratch resistance.

[0120] The above are only preferred embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural transformations made using the contents of the present description and drawings under the inventive concept of the present invention, or direct / indirect applications in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A metal cooking utensil, characterized in that: include: a metal base layer having a concave-convex texture structure in the form of bionic leaf veins, the concave-convex texture structure comprising a plurality of rib units and concave units formed between the rib units, wherein the planar projection shapes of any two adjacent rib units in a direction perpendicular to the surface of the metal base layer are different from each other; A nanoparticle layer conformally covers the surface of the concave-convex texture structure; The hydrophobic material layer conformally covers the surface of the nanoparticle layer.

2. The metal cooking utensil according to claim 1, wherein: The depth of the recessed unit does not exceed one quarter of the thickness of the metal base layer; and / or the depth of the recessed unit ranges from 10 μm to 100 μm.

3. The metal cooking utensil according to claim 1, wherein: The nanoparticle layer contains nanoparticles, the material of the nanoparticles includes at least one of elemental silicon, silicon oxide, silicon nitride, tungsten nitride, and zirconium nitride, and the particle size of the nanoparticles ranges from 50 nm to 1000 nm.

4. The metal cooking utensil according to claim 3, wherein: The projection area coverage of the nanoparticles on the surface of the concavo-convex texture structure along the vertical direction is 20%-90%.

5. The metal cooking utensil according to claim 1, wherein: The thickness of the nanoparticle layer is in the range of 0.05 μm to 2 μm; and / or the thickness of the hydrophobic material layer is in the range of 0.05 μm to 5 μm.

6. The metal cooking utensil according to claim 1, wherein: The hydrophobic material layer is made of at least one of an organic silicon polymer, a fluorine-containing polymer, and ceramics.

7. The metal cooking utensil according to claim 1, wherein: The material of the metal base layer includes at least one of iron, stainless steel, aluminum, copper, and titanium, and / or the metal base layer includes a multi-layer structure.

8. The metal cooking utensil according to any one of claims 1 to 7, characterized in that: The concave-convex texture structure includes a micron structure, and the micron structure is distributed on the surface of the metal base layer; The nanoparticle layer covers at least a portion of the microstructure to form a micro-nanostructure; Wherein, polar covalent bonds are formed between the hydrophobic material layer and the micro-nanostructure.

9. A method for preparing a metal cooking utensil according to any one of claims 1 to 7, characterized in that: The following steps are involved: A concave-convex texture structure in the form of bionic leaf veins is formed on the surface of the metal substrate by one of embossing, etching, laser or roughening processes; Depositing a nanoparticle layer on the surface of the concavo-convex texture structure; A hydrophobic material layer is deposited on the surface of the nanoparticle layer by spraying, dipping or evaporation coating.

10. The method for preparing a metal cooking utensil according to claim 9, wherein: In the step of depositing a nanoparticle layer on the surface of the concavo-convex texture structure, the deposition conditions include: vacuum degree 0.01Pa-0.2Pa, substrate bias 150V-600V; target current 70-90A, temperature 100-200°C.

Citation Information

Patent Citations

  • Nonstick cookware and manufacturing method thereof

    CN102641078A

  • Non-stick material and non-stick coating

    CN117702039A

  • Composite sheet, inner container, cooking utensil and manufacturing method of composite sheet

    CN119332203A

  • Physical non-stick structure, cooking utensil and processing method

    CN119488228A

  • 0-coating rice cooking utensil and 0-coating rice cooker

    CN222149766U

Cited By

  • Wear-resistant stainless steel plate and preparation method thereof

    CN120839069A